ANALISIS KOMUNIKASI, PENGEMBANGAN PEGAWAI DAN MOTIVASI TERHADAP SEMANGAT KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN ACEH BARAT DAYA - Yuni Eliza (Warmadewa Management and Business Journal (WMBJ), 2023)
The role of effective communication in developing and motivating employees is very important in increasing employee morale because these three variables support good working conditions. The purpose of this study is to analyze the impact of communication, employee development, and moral motivation toward employe morale at regional secretariat of Aceh Barat Daya. The population used in this study was about 102 employees. In this study, data collection techniques used was questioner data. This data was analyzed by using multiple regression analysis. The results showed that communication had a partial positive and significant effect on employee morale at the Aceh Barat Daya Regional Secretariat. Associated with the morale of the employees of the Aceh Barat Daya Regional Secretariat At the same time (Test F), communication, development and motivation of employees at the Aceh Barat Daya Regional Secretariat have a positive and significant effect on employee morale.